John Cage ou les histoires du doute - Vincent Broqua (Transatlantica)
John Cage’s Silence defines experimentalism: it both delineates and practices a theory of experimentalism. It is an aesthetic theory as much as an aesthetic of theory. The present article shows the importance of the stories that Cage disseminated throughout the book. In spite of their marginal situation in Silence, they turn out to be a pivotal performance of Cage’s experimentalism informed by his philosophical skepticism.